The Foreign Policy of the President of Lithuania towards Poland in the context of security in 2019–2023 - Malużinas Martinas (2024)
The aim of this article is to analyse the Lithuanian foreign policy pursued by the President of the Republic of Lithuania, Gitanas Nausda, towards Poland in the years 2019–2023 and to attempt to assess the main directions of its activities in this aspect.